Analisis Capaian Pembelajaran Mata Kuliah Keterampilan Interpersonal bagi Mahasiswa dalam Meningkatkan Komunikasi dan Pengembangan Profesional - Yani Parti Astuti; Erlin Dolphina; Dewi Agustini Santoso; T.Sutojo; Erna Zuni Astuti; Edy Mulyanto; Sindhu Rakasiwi (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
In today's world, many young individuals still lack effective communication skills, a trend that is evident among university students, particularly those from Generation Z. These students, despite having access to technology and social media, are often not taught how to communicate in a professional and respectful manner. This paper discusses the importance of communication skills and their development through the Interpersonal Skills (KI) course. Within this course, students not only develop communication abilities but also both soft and hard skills essential for their personal and professional growth. The course includes various assessments, one of which is the Community Service (PKM) output. This PKM aims to provide students with practical experience in communication by engaging with external partners and presenting ideas related to their academic programs. The activities conducted under this PKM serve as an assignment for the course, contributing to grades for assignments, Mid-Semester Exams (UTS), and Final Semester Exams (UAS). Students are tasked with creating proposals, reports, posters, and videos as part of the assignment, and for the UTS, they present proposals to their partners. The UAS grade is based on the final report presentation, showcasing the results of their PKM activities. Through the KI course, students gain valuable experience in communicating with external partners, collaborating in teams, and presenting their work confidently in front of their peers. These activities not only enhance students' communication skills but also foster leadership qualities and teamwork, preparing them for professional environments. Thus, the KI course plays a crucial role in developing interpersonal communication skills that are essential in today's interconnected world.